Complete response to BRICS in Locally advanced pancreatic cancer (pMMR, CPS 30): a case report - Yang, Songlong; Shao, Liangxiu; Wu, Yating; Peng, Yonghai; Fan, Weiqiang (Frontiers in Immunology, 2026)
BackgroundLocally advanced pancreatic cancer (LAPC) has a dismal prognosis, marked by an exceedingly low 5-year survival rate. While immune checkpoint inhibitors (ICIs) have demonstrated efficacy across various solid tumors, their application in the treatment of pancreatic ductal adenocarcinoma—particularly in mismatch repair–proficient (pMMR) cases—is restricted by the immunosuppressive nature of the tumor microenvironment (TME). Thus, more effective treatment strategies for pMMR LAPC are urgently needed.Case presentationWe present a 65-year-old female diagnosed with LAPC (cT4N1M0, Stage III), confirmed pathologically as pancreatic ductal adenocarcinoma with pMMR status and a high programmed death-ligand 1 (PD-L1) combined positive score (CPS) of 30. Initial tumor markers were significantly elevated (CA19-9: 62,228.8 U/L; CEA: 100 ng/mL). The patient received a novel multimodal treatment referred to as the BRICS Regimen, an acronym derived from Bifidobacterium supplementation, Radiotherapy (hypofractionated), Immunotherapy (PD-1 inhibitors), Chemotherapy (low-dose), and Stereotactic approach. This protocol can be modified to match the individual disease characteristics. In this case, the treatment comprised SBRT 24 Gy/3 fractions → q21d toripalimab 240 mg + nab-paclitaxel 200→100 mg + anlotinib 12 mg d1–14, with continuous Bifidobacterium triple viable tablets. Imaging following treatment indicated a complete response (CR), and tumor markers remained normal for 5 months post-therapy. The treatment was well tolerated, with no severe adverse events reported.ConclusionThis report suggests that a combined modality approach—integrating SBRT, chemotherapy, antiangiogenic therapy, ICI, and probiotics—may achieve CR in patients presenting with pMMR LAPC and high PD-L1 expression, even without surgery. These results challenge the prevailing assumption that pMMR status invariably predicts resistance to immunotherapy. These findings suggest that, in pMMR pancreatic cancers with high PD-L1 CPS, multimodal treatment strategies may remodel the tumor microenvironment and overcome immune resistance, highlighting a promising therapeutic direction.